2010
DOI: 10.1002/j.1551-8833.2010.tb11337.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving resilience against the effects of climate change

Abstract: Water, wastewater, and stormwater infrastructure are particularly vulnerable to sea level rise and other effects of climate change, especially in low coastal regions such as south Florida. Alternative water and wastewater recovery programs that work now may not be applicable in 100 years. Florida Atlantic University evaluated options that the water utility in the coastal community of the city of Pompano Beach, Fla., could apply to improve resilience to climate change effects. Immediate issues were that groundw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…As a result, these projections were used as a basis for SLR projections. It was noted that the mid-range level of 3 feet is critical for low-lying coastal areas like southeast Florida where over half the urban areas has elevations below 5 feet National Geodetic Vertical Datum of 1929 (NGVD), making it highly vulnerable to inundation since mean high tide is approximately 2 feet above mean tide (Bloetscher et al, 2010(Bloetscher et al, , 2012. As a result, water, sewer, stormwater and transportation infrastructure in low-lying areas could be compromised.…”
Section: Match the Us Army Corps Ofmentioning
confidence: 99%
“…As a result, these projections were used as a basis for SLR projections. It was noted that the mid-range level of 3 feet is critical for low-lying coastal areas like southeast Florida where over half the urban areas has elevations below 5 feet National Geodetic Vertical Datum of 1929 (NGVD), making it highly vulnerable to inundation since mean high tide is approximately 2 feet above mean tide (Bloetscher et al, 2010(Bloetscher et al, , 2012. As a result, water, sewer, stormwater and transportation infrastructure in low-lying areas could be compromised.…”
Section: Match the Us Army Corps Ofmentioning
confidence: 99%
“…The UN has identified that a high probability exists for rising sea levels to contaminate and subsequently reduce adequate freshwater supplies in Bangladesh, Egypt, and Thailand (UN, 2006). Bloetscher et al (2010) includes a case focused on mitigating climate change impacts on coastal water supplies and infrastructure. Additionally, with ice cap melting and subsequent sea level rise, stormwater infrastructure at low-lying, shallow elevations may not have the capacity to contain the rainfall events themselves, nor convey the rate of stormwater flow to outfalls, nor be physically capable of discharging if sea levels rise significantly enough to obstruct stormwater outfalls.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The top-down approach involves refining predictions of climate change, downscaling of climate models to apply them to local geographies and streamflow situations, and eventual IWRM planning (Miller et al, 2005). Some of this downscaling of models to local streamflows has progressed, including developing a transferable model of the process to expand applications (Bloetscher et al, 2010, Colorado Water Conservation Board [CWCB], 2011, King County, 2007, and Means et al, 2010. To address the high uncertainty associated with the timing and possible magnitude thresholds of climate impacts, Cromwell et al (2010a) proposes a third questions to guide the analysis: "What is the overall adaptation strategy that leads to more sustainable infrastructure over the course of this century -the sustainable path?"…”
Section: Climate Adaptation Planning To Incorporate Risk and Climate mentioning
confidence: 99%
See 2 more Smart Citations